(untitled) (The Review of Diabetic Studies, 2024)
Blood acidosis, especially diabetic ketoacidosis (DCA), is one of the most important acute metabolic emergencies in patients with diabetes and can rapidly become life-threatening if not recognized and treated in time [1]. DCA is characterized by uncontrolled hyperglycemia, ketone accumulation, and systemic metabolic acidosis, usually triggered by infection, missed insulin doses, or other acute stressors such as myocardial infarction or severe illness [2]. In the hospital setting, effective management of DCA depends on three main pillars: early diagnosis, structured treatment, and continuous monitoring. Diagnosis is based on clinical assessment combined with blood tests that confirm hyperglycemia, ketonemia or ketonuria, and metabolic acidosis [1]. Treatment focuses on prompt intravenous fluid resuscitation, appropriate insulin therapy to stop ketone production, and careful correction of electrolyte disturbances, with special attention to potassium balance to avoid serious cardiac complications [3]. At the same time, the underlying precipitating factor, such as infection or non-adherence to insulin, must be identified and managed to prevent recurrence [2]. Continuous monitoring of vital signs, blood glucose, acid-base status, and electrolytes is essential to follow the course of recovery and detect complications early. This paper describes practical, hospital-based strategies for the diagnosis, treatment, and monitoring of blood acidosis in the form of DCA, using a clear descriptive approach suitable for clinical application and non-specialist review committees [1–3].